2018
DOI: 10.2166/ws.2018.189
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of a GR4J model and wavelet-based artificial neural network for rainfall–runoff modelling

Abstract: Data-driven models and conceptual models have been utilized in an attempt to perform rainfall–runoff modelling. The aim of this study is comparing the performance of an artificial neural network (ANN) model, wavelet-based artificial neural network (WANN) model and GR4J lumped daily conceptual model for rainfall–runoff modelling of two rivers in the USA. It was obtained that the performance of the data-driven models (ANN, WANN) is better than the GR4J model especially when streamflow data the preceding day (Qt-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For the PC‐based representation, we chose the GR4J dynamical lumped water balance model (Perrin et al., 2003), due to its relative parsimony and the reports of good performance in other studies (Kunnath‐Poovakka & Eldho, 2019; Pagano et al., 2010; Sezen & Partal, 2019), and because the catchment‐scale data required for its implementation is available (Table A1). Moreover, we coupled to it the lumped CemaNeige snowmelt module (Valéry et al., 2014) to account for snow process dynamics at high altitudes in Andes Mountain range.…”
Section: Study Methodologymentioning
confidence: 99%
“…For the PC‐based representation, we chose the GR4J dynamical lumped water balance model (Perrin et al., 2003), due to its relative parsimony and the reports of good performance in other studies (Kunnath‐Poovakka & Eldho, 2019; Pagano et al., 2010; Sezen & Partal, 2019), and because the catchment‐scale data required for its implementation is available (Table A1). Moreover, we coupled to it the lumped CemaNeige snowmelt module (Valéry et al., 2014) to account for snow process dynamics at high altitudes in Andes Mountain range.…”
Section: Study Methodologymentioning
confidence: 99%
“…Our previous work (Pan et al, 2020) verified that the ACWSC (i.e., parameter θ 1 ) had an "abrupt" point after the prolonged meteorological drought, which assumes that the offset of the estimated θ 1 represents the change in the ACWSC. Meanwhile, θ 1 in each period is recognized as a constant value and does not include the periodicity of the ACWSC that was outlined by many previous works (Nepal et al, 2017;Kunnath-Poovakka and Eldho, 2019;Sezen and Partal, 2019). However, Westra et al (2014) and Pan et al (2020) indicated that the ACWSC had periodic variability that may be due to the seasonal growth and wiling of catchment vegetation.…”
Section: Periodicity Of the Acwscmentioning
confidence: 95%
“…The GR4J model was used to address the response of the ACWSC to prolonged meteorological drought. The model processes a relatively simple structure with relatively low requirements for input data, and it has been widely used in the rainfall-runoff simulation for small and medium-sized catchments (Demirel et al, 2013;Sezen and Partal, 2019;Kunnath-Poovakka and Eldho, 2019). However, the GR4J model is implemented subject to restrictions and limitations due to the inadequate description of the runoff generation and flow confluence processes in large catchments (e.g., larger than 10 000 km 2 ).…”
Section: Limitations Of the Hydrological Modelmentioning
confidence: 99%
“…Our previous work (Pan et al, 2020) has verified that the CWSC (i.e., parameter θ1) had an "abrupt" point after the prolonged meteorological drought, which assumes that the offset of the estimated θ1 represents the change of CWSC. Meanwhile, the θ1 in each period is recognized as a constant value and do not include the periodicity of the CWSC that has been outlined by many previous works (Nepal et al, 2017;Kunnath-Poovakka and Eldho, 2019;Sezen and Partal, 2019).…”
Section: Periodicity Of the Cwscmentioning
confidence: 99%